(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
Recieps of innovative types of fermented milk cheese and cottage cheese products for healthy food have been proposed, scientifically substantiated and developed. Herbal mixtures were used as an innovation in their production. The recipes of herbal mixtures consist of fruit and vegetable additives obtained by deep processing methods from traditional types of vegetable raw materials (pumpkin, carrot, sweet pepper, garlic, parsley root, celery root) in the form of cryopastes, as well as fruit and vegetable additives from other types of traditional raw materials (black currant, beet, apples, lemons) in the form of finely dispersed powders. Fruit and vegetable additives are distinguished by a high content of biologically active phytocomponents with health-promoting effects (natural coloring agents, aromatic substances, dietary fiber, etc.). The presence of these substances in the product eliminates the need to use traditional food additives (coloring, flavoring and structuring agents), which can negatively affect human health. It is shown that fruit and vegetable additives obtained by deep processing methods from traditional types of raw materials in the form of cryopastes and finely dispersed powders are sources of natural biologically active phytocomponents that contribute to strengthening the body’s defenses. Recieps of frozen and powdered vegetable mixtures have been developed, which differ in the types and ratio of cryo- and powdered fruit and vegetable additives, respectively. The resulting mixtures are characterized by a high content of biologically active phytocomponents and do not contain synthetic food additives. The resulting mixtures are used in the development of innovative types of fermented milk cheese and cottage cheese products for healthy nutrition.